Analysis of Migrant Worker Family’s Financial Management - Agustin, Grisvia; Wahyono, Hari; Dwi Satrio, Yogi; Munir, Syahrul; Rah- mawati, Dian; Kustiandi, Januar (KnE Social Sciences, 2020)
Worker migration is an old phenomenon. Many workers from Indonesia had migrated since 1970s, legally and illegally. According data from OECD (September, 2015) there are an estimated 215 million international migrants working in a globalised economy, the majority of whom are remitting money to their home country. Remittances are vital component of household income for families, reducing poverty and creating opportunities for investment in education and enterprise. As we know, high-income countries are the main sources of remittances. Government wants to upgrade the migrant workers financial knowledge to reduce revel tendency. But the one who arranges the remittance is the one in family member, not the migrant worker. This study tend to analyze ability to manage remittance and financial of migrant worker’s family using descriptive qualitative method based on worker migration and basic financial management theory. The results are remittances from abroad generally received 3-4 monthly. Remittances in dollars or others foreign exchange rate (for example developed countries) has huge value in rupiah because of rupiah’s exchange rate depreciation tendency. But in East Java, Indonesia, access to increase financial literacy for migrant workers family is very lack. Migrant worker’s family may have proper education and internet access but don’t improve their financial literacy. Keywords: remittance, family’s financial management, Indonesia migrant worker